The sensory and nutrient analysis by the addition of Chia Seed (Salvia hispanica L.) to Star fruit juice (Averrhoa carambola L.) as a drink for hypertension patients - Erlinda, Yuni; Marliyati, Sri Anna; Setiawan, Budi (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Hypertension, when it is not controlled, can cause complications to many diseases and death. Hypertension control can be achieved by adjusting to a healthy diet, such as increasing the consumption of fruit, whole grains, potassium intake, calcium, and magnesium. Several studies have shown that star fruit and chia seeds can control blood pressure in people with hypertension. However, the nutritional content, such as calcium and magnesium, is still relatively low in star fruit. According to USDA, chia seeds contain high level of calcium, potassium, and magnesium.Objectives: This research aims to determine the sensory acceptability and the nutritional content of star fruit juice by adding chia seeds.Methods: This is an experimental study with a Completely Randomized Design (CRD). There were four formulations of star fruit juice with chia seeds additions (0 g,10 g,15 g, and 20 g). The sensory analysis was tested by the Kruskal Wallis test and Mann-Whitney test. While differences of the nutritional content from the product that preferred by panelists were tested by Independent T-test.Results: There were significant differences (p<0.05) in all sensory parameters. The selected sweet star fruit juice with the addition 10 g chia seed formulation showed an increase in nutrients except for the water content. Water content of 89.21 %, ash content of 0.32 %, carbohydrate content of 7.14 %, fat content of 1.75 %, protein content of 1.55%, potassium content of 206 mg/200 ml, calcium content of 34.84 mg/200 ml, magnesium content of 17.80 mg/200 ml, and sodium content of 2.46 mg/200 ml.Conclusions: Sweet start fruit juice with the addition of 10 g of chia seed is the most liked star fruit juice formulation with chia seed addition by the research panellists, and it can increase the nutritional content, especially calcium and magnesium content.